Takhrij and Syarah Hadith of Agrotechnology: Content and Benefits of Dates - Anur Wulan; Wahyudin Darmalaksana; Anna Aina Roosda (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with regard to dates. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study are dates which are recommended to eat them in the morning. The content and benefits of dates when consuming them have been known from several studies. The conclusion of this research is takhrij and syarah hadith of the Prophet Muhammad SAW about dates with agrotechnology analysis informs that the content of dates is beneficial for human health.